2021
DOI: 10.1038/s41598-021-00014-1
|View full text |Cite
|
Sign up to set email alerts
|

Faecal miRNA profiles associated with age, sex, BMI, and lifestyle habits in healthy individuals

Abstract: For their stability and detectability faecal microRNAs represent promising molecules with potential clinical interest as non-invasive diagnostic and prognostic biomarkers. However, there is no evidence on how stool miRNA profiles change according to an individual’s age, sex, and body mass index (BMI) or how lifestyle habits influence the expression levels of these molecules. We explored the relationship between the stool miRNA levels and common traits (sex, age, BMI, and menopausal status) or lifestyle habits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Accumulating evidence associated specific nutrient intake with miRNA expression. 13 , 14 In particular, our group previously reported that fecal miRNA profiles change with anthropometric traits and lifestyle habits 15 as well as accurately distinguish subjects with different dietary habits. 16 In this respect, miRNAs could also reflect the impact of the GFD on CD subjects.…”
Section: Introductionmentioning
confidence: 92%
“…Accumulating evidence associated specific nutrient intake with miRNA expression. 13 , 14 In particular, our group previously reported that fecal miRNA profiles change with anthropometric traits and lifestyle habits 15 as well as accurately distinguish subjects with different dietary habits. 16 In this respect, miRNAs could also reflect the impact of the GFD on CD subjects.…”
Section: Introductionmentioning
confidence: 92%
“…The authors found that miRNA-8074 levels decreased with age (−0.26, adj. p < 0.001) [ 63 ]. Kolhe et al noted that synovial fluid exosomal miRNA-8074 is down-regulated in females with osteoarthritis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Libraries were pooled together (in 24‐plex) and further purified with a gel size selection. A final Bioanalyzer® 2100 run with the High Sensitivity DNA Kit (Agilent Technologies) allowed to assess DNA libraries quality regarding size, purity, and concentration 24 . The obtained libraries were subjected to the Illumina® sequencing pipeline, passing through clonal cluster generation on a single‐read flow cell (Illumina) by bridge amplification on the cBot (TruSeq SR Cluster Kit v3‐cBOT‐HS, Illumina) and 50 cycles sequencing‐by‐synthesis on the HiSeq™ 2000 Sequencing System (Illumina) (in collaboration with EMBL, Gene core facility).…”
Section: Methodsmentioning
confidence: 99%